Exploring the Impact of Computer RPG Game-Based Teaching Modules on Environmental Education for Eighth-Grade Junior High School Students - Hsieh, Yi‑Lin; Yeh, Shin-Cheng (Journal of Ecohumanism, 2025)
This study aims to explore the changes in the cognition, attitudes, and behaviors of eighth-grade students regarding environmental and marine conservation after being taught using a computer-based RPG (Role-playing game) instructional module. The participants were divided into an experimental group and a control group. The control group received traditional instruction, while the experimental group used a course module designed for this study. This module was adapted based on the concept of the Fish Banks game, and the researcher developed a computer RPG game called "Ocean Domination" for the instruction. The results of the study revealed that, among the five environmental education competency indicators, the experimental group, which used the computer RPG game-based instructional module, showed significant improvement in environmental awareness and sensitivity, environmental conceptual knowledge, and environmental action experience. In contrast, the group that used traditional instruction did not show significant progress. Both groups exhibited significant improvement in environmental values and attitudes, as well as environmental action skills, with the experimental group's progress being higher than that of the traditional instruction group. Additionally, the experimental group demonstrated a significant improvement in interest in environmental course learning, whereas the traditional instruction group did not. In summary, the computer RPG game-based instructional module developed in this study had a positive impact on the cognition, affect, and skills of eighth-grade students in terms of environmental conservation.